The Influence Of Product, Price, Brand Image, And Product Quality On Consumer Purchasing Interest For Oppo Cell Phones At Semaku Ponsel Manna Counter In South Bengkulu - Kencana, Putri; Irwanto , Tito; Hidayah , Nenden Restu (Universitas Dehasen Bengkulu, 2024)
People are more interested in and using smartphones more than other communication devices because they are easy to carry and can be used whenever needed. Currently, there is an increasing demand for smartphones, presenting an opportunity for smartphone manufacturers to innovate in producing new phones. The purpose of this study is to determine the influence of product, price, brand image, and product quality on consumer buying interest in OPPO smartphones at Semaku Ponsel Manna counter in South Bengkulu. The analysis methods used in this study include Validity Test, Reliability Test, Multiple Linear Regression Analysis, coefficient of determination, and hypothesis testing using t-test and f-test with a sample size of 75 questionnaires to OPPO smartphone buyers at Semaku Ponsel Manna counter in South Bengkulu. The results of the multiple linear regression analysis show the equation Y = 6.143 + 0.160 X1 + 0.323 X2 + 0.196 X3 + 0.215 X4. This indicates a positive regression direction, meaning that the variables product quality (X1), Price (X2), Brand Image (X3), and Product Quality (X4) have a positive influence on Buying Interest (Y) at Semaku Ponsel Manna counter in South Bengkulu. The coefficient of determination value from the calculation using SPSS shows an R square value of 71.9%. This means that the values of Product (X1), Price (X2), Brand image (X3), and Product Quality (X4) influence the buying interest (Y) by 71.9%, while the remaining 28.1% is influenced by other variables not studied in the research.